Trophic Structure of Jaguar Cichilid (Parachromis Managuensis) Caught In Penjalin Reservoir, Central Java - Alamsyah, Zuhaeri Surya Ananda; Putri, Adinda Kurnia; Sanjayasari, Dyahruri (Journal Of Artha Biological Engineering, 2025)
The jaguar cichlid Parachromis managuensis (Günther, 1867) or withthe local name marsella fish is a native fish originating from CentralAmerican waters but has been introduced to several countries such asNorth America, South America and Southeast Asia. This research aimsto provide the information about the food preference and trophicstructure of jaguar fish from Penjalin Reservoir. The method in thisresearch uses the calculation of the Index of Preponderance (IP) anddetermining the trophic level. The study revealed that the average foodcomposition of jaguar fish consists of 82.29% fish pieces, 4.70% insectpieces, 0.18% zooplankton pieces, 2.25% gastropods pieces and 10.62%detritus. The overall average trophic level value for fish is 4.22 (TL5) orcarnivorous fish.